Peran Kepemimpinan Kepala Madrasah dalam Meningkatkan Mutu Pendidikan Islam - Munardji (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2013)
Achievement of the objectives of education is very dependent on the skill and wisdom of the principal's leadership is one of the leaders of education. Because the principal is a professional officer in the school organization responsible for the regulation of all sources of the organization and collaborate with teachers in educating students to achieve educational goals. With the professionalism of this principal professional development of educational personnel is easily done because according to function, to understand the needs of school principals who he led to the competence of teachers not only stagnates the competence he had previously, but grew and developed so well that the professionalism of teachers will be realized.